Higher risk of cam regrowth in adolescents undergoing arthroscopic femoroacetabular impingement correction: a retrospective comparison of 33 adolescent and 74 adults - Arashi, Tomoya; Murata, Yoichi; Utsunomiya, Hajime; Kanezaki, Shiho; Suzuki, Hitoshi; Sakai, Akinori; Uchida, Soshi (Acta Orthopaedica, 2019)
Background and purpose — The current literature does not clarify the predictors of cam regrowth and poor clinical outcome following hip arthroscopic femoroacetabular impingement (FAI) correction surgery. Therefore, we investigated the prevalence and risk factors of cam regrowth following arthroscopic FAI correction surgery in skeletally immature patients compared with skeletally mature patients. Patients and methods — 33 teenagers (36 hips as 4 underwent bilateral hip arthroscopies, average age 16.7 [SD 1.6] years, 21 boys [22 hips], 12 girls [14 hips]) undergoing arthroscopic FAI correction and 74 adult controls (74 hips, average age 41 [SD 12] years, 42 men [42 hips], 32 women [32 hips]) were retrospectively reviewed. Postoperative radiographs were obtained, and cam regrowth was evaluated. Clinical characteristics, radiographic findings, arthroscopic findings, and procedures between skeletally immature (SI) and mature (SM) patients were compared. Average follow-up period was 28 months in the SI group and 24 months in the SM group. Results — Preoperatively, 27 of 36 hips were SI, having either a Risser sign grade ≤ 4 of iliac apophysis or open physes of the proximal femur. Cam regrowth was present in 4 of 27 SI hips. The number of cam regrowth cases was significantly higher in SI patients than in SM patients (0/74 hips). 6 patients required revision hip arthroscopic surgeries (4 men: FAI recurrence due to cam regrowth; 2 women: capsulolabral adhesions). At the last follow-up, the mean modified Harris hip score and nonarthritic hip score were significantly improved postoperatively. Interpretation — 4 of 27 SI hips (95% CI 0.04–0.3) had bone regrowth after cam resection arthroscopically. Our case series showed a non-negligible risk of cam regrowth in SI patients, especially in male patients and patients aged approximately 15 years.